STRATEGIES OF WOMEN LEADERSHIP IN CHANGING TEACHER PERFORMANCE (CASE STUDY AT MI NUR HIDAYAH WONOSARI KLATEN) - SAFITRI, PINASTI ELOK (ACADEMIA: Jurnal Inovasi Riset Akademik, 2024)
This study discusses the strategy of women's leadership in improving teacher performance at MI Nur Hidayah. The main objective of this study is to identify the leadership applied and the approach used by female leaders in enhancing the performance of educators in educational institutions. Based on the research conducted, it can be observed that the indicators of performance improvement can be achieved through the women's leadership implemented at MI Nur Hidayah. The strategy applied involves establishing communication through routine activities, openness, and a mutual support attitude. This study is qualitative, using an approach based on interviews and observations. It was conducted to confirm that women are capable of being leaders who create an actively supportive work environment, thus improving teacher performance optimally to achieve maximum results. ABSTRAKPenelitian ini membahas strategi kepemimpinan perempuan dalam meningkatkan kinerja guru di MI Nur Hidayah. Tujuan utama dari penelitian ini adalah untuk mengidentifikasi kepemimpinan yang diterapkan dan pendekatan yang digunakan oleh pemimpin perempuan dalam meningkatkan kinerja pendidik di lembaga pendidikan. Berdasarkan penelitian yang dilakukan, dapat dilihat bahwa indikator-indikator peningkatan kinerja dapat tercapai dengan kepemimpinan perempuan yang diterapkan di MI Nur Hidayah. Strategi yang diterapkan adalah membangun komunikasi melalui kegiatan rutin, keterbukaan, dan sikap saling mendukung satu sama lain. Penelitian ini bersifat kualitatif dengan menggunakan pendekatan melalui wawancara dan observasi. Penelitian ini dilakukan untuk mengonfirmasi bahwa perempuan mampu menjadi pemimpin yang menciptakan lingkungan kerja yang aktif dan mendukung, sehingga dapat meningkatkan kinerja guru secara optimal untuk mencapai hasil yang maksimal.